Class Action as the Method of Managing a Multi - Party Civil Procedure - Васильева, Татьяна Андреевна Андреевна (Teisė, 2018)
[full article in Russian; abstract in English] The article is devoted to the definition of the legal nature of class action. The construction of class action is analyzed in the context of a multi-party civil procedure. Having considered the legal regulation of certain types of class action, the author came to the conclusion that the class action is the modified multi-party civil litigation.